In Vitro Ability of a Novel Nanohydroxyapatite Oral Rinse to Occlude Dentine Tubules - Robert G. Hill; Xiaohui Chen; David G. Gillam (International Journal of Dentistry)
Objectives. The aim of the study was to investigate the ability of a novel nanohydroxyapatite (nHA) desensitizing oral rinse to occlude dentine tubules compared to selected commercially available desensitizing oral rinses. Methods. 25 caries-free extracted molars were sectioned into 1 mm thick dentine discs. The dentine discs (n=25) were etched with 6% citric acid for 2 minutes and rinsed with distilled water, prior to a 30-second application of test and control oral rinses. Evaluation was by (1) Scanning Electron Microscopy (SEM) of the dentine surface and (2) fluid flow measurements through a dentine disc. Results. Most of the oral rinses failed to adequately cover the dentine surface apart from the nHa oral rinse. However the hydroxyapatite, 1.4% potassium oxalate, and arginine/PVM/MA copolymer oral rinses, appeared to be relatively more effective than the nHA test and negative control rinses (potassium nitrate) in relation to a reduction in fluid flow measurements. Conclusions. Although the novel nHA oral rinse demonstrated the ability to occlude the dentine tubules and reduce the fluid flow measurements, some of the other oral rinses appeared to demonstrate a statistically significant reduction in fluid flow through the dentine disc, in particular the arginine/PVM/MA copolymer oral rinse.